Graduating into a downturn: Are physicians recession proof?. (29th June 2017) - Chen, Alice; Sasso, Anthony Lo; Richards, Michael R.
Abstract: An extensive literature documents immediate and persistent adverse labor market outcomes for individuals graduating into an economic downturn, but these effects are heterogeneous across sectors, occupations, and skill levels. In particular, the impact of recessions on the labor market outcomes for new physician graduates remains unknown. We leverage a unique dataset on New York physicians to analyze if and how the Great Recession impacted the labor market of physicians who have completed their residency and fellowship training and are seeking their first job. We find that these physicians do not delay labor market entry and their job searches and other employment outcomes are unaffected by the business cycle. The collage of evidence demonstrates that new graduates were largely unfazed by the recent downturn, which sharply contrasts with other highly educated, high remunerating occupations.